The difficulties that face Sixth Grade students in Riyadh in solving the mathematical problem and their causes from their point of view - AlAsmari, Zayed Saeed; Al- Babtain, Ibrahim Abd El- Wahab (Journal of Educational and Psychological Sciences, 2020)
The aim of this research is to identify the difficulties facing sixth- grade primary students in Riyadh in solving the mathematical problem and their causes. The researcher used the descriptive survey method, and the researcher applied two tools to find out that it is a diagnostic test and an interview where the test was applied to a sample of (125) students and then applied the interview to a random sample consisting of (20) students in the sixth grade in the city of Riyadh. Where the results reached indicated the following:Students in understanding, planning and implementing the mathematical problem got a percentage of (23.36%), i.e. an estimate (low), with regard to the percentage of their success in health from the problem solving the mathematical problem (24,24%), with an estimate (very low).Difficulties faced by sixth-graders in the city of Riyadh in solving the mathematical problem, as they were: Identify the unknown and required in the mathematical problem, then make sure of enough information given to solve the mathematical problem; They were followed by determining the strategies that will be used for the solution, then the student is not convinced of the importance of following the four steps to solve the mathematical problem, and finally, the mathematics teacher focuses on the step of implementing the mathematical problem solution only. According to the results, a number of recommendations and proposals were presented to overcome the difficulties facing students in solving the mathematical issue in Riyadh and the whole of the Kingdom.
Keywords: causes of difficulties; Primary sixth pupils; Riyadh city; Mathematical issue